THE STATUS OF THE INDUCTIVE METHOD IN EDUCATION AND ITS IMPACT ON ACADEMIC ACHIEVEMENT: A COMPARATIVE STUDY BETWEEN ARABIC LANGUAGE AND SCIENCE EDUCATION - Salah Ouchen; Zedira Khammar (International Journal of Innovative Technologies in Social Science, 2025)
This research aims to enhance teachers’ pedagogical practices and improve their professional performance. To achieve this objective, the researcher employed multiple methods, particularly descriptive and comparative approaches, combining a survey study with a practical field study. The sample consisted of 20 teachers out of 100 and 24 students out of 500. Data were analyzed using statistical variance methods to examine the relationship between academic achievement and the effectiveness of teaching methods. The findings indicate that teaching Arabic grammar and science education both rely on the inductive method. The use of induction was found to account for 14.89% - a statistically significant result, as it exceeds the critical values of 4.05 and 7.21 at the 5% and 1% confidence levels, respectively. Despite differences in subject matter and methodological approaches, both disciplines utilize induction - systematic induction in the case of Arabic grammar, and experimental induction in the case of scientific education - each tailored to the nature of the subject.